(untitled) (Bangladesh Journal of Otorhinolaryngology, 2012)
Childhood carcinoma larynx is a very rare clinical entity. A girl of 10 year-old presented with persistent and progressive sore throat with dysphagia, change of voice and respiratory distress with stridor which needed tracheostomy and nasogastric tube feeding. Indirect laryngoscopy revealed exophytic growth involving the epiglottis and ary-epiglottic folds, restricted movement of hemilarynx and compromised airway. Biopsies were positive for squamous cell carcinoma. The malnourished cachectic poor patient was referred for receiving radiotherapy. A high index of suspicion is necessary to make the diagnosis since consequences of late diagnosis are very serious. This report underscores the need for prompt evaluation of children with persistent and progressive sore throat with dysphagia. DOI: http://dx.doi.org/10.3329/bjo.v18i1.10422 Bangladesh J Otorhinolaryngol 2012; 18(1): 68-73